Data Science: Trends and Its Role in Various Fields - Iskamto, Dedi (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2023)
Data Science is a field that has developed rapidly in recent years, which utilizes technology and data analysis methods to produce useful information for various fields. In this paper, we will explain the latest trends in the field of Data Science and their role in various fields, including the fields of business, health, finance, and the public sector and discuss the technologies and algorithms used in Data Science, such as Machine Learning, Natural language Processing., data visualization, Big Data Analytics, and provides examples of how this technology can be used to solve problems in various fields. This paper aims to explore that Data Science has a very important role in various fields, and will continue to develop along with technological developments. The literature study methodology was carried out to collect data and information related to this topic, which aims to ensure that the data analysis carried out is accurate, and can be trusted. The results of the study found that Data Science science and technology has helped a number of parties with its application to certain aspects related to their fields. Thus, this paper can be a useful source of information for professionals and researchers who are interested in Data Science and its role in various fields.